Increasing the Focus on Children's Complex and Integrated Care Needs: A Position Paper of the European Academy of Pediatrics - Maria Brenner; Maria Brenner; Josephine Greene; Carmel Doyle; Carmel Doyle; Berthold Koletzko; Berthold Koletzko; Stefano del Torso; Stefano del Torso; Ivan Bambir; Ivan Bambir; Ann De Guchtenaere; et al. (Frontiers Media S.A., 2021)
There is wide variation in terminology used to refer to children living with complex needs, across clinical, research and policy settings. It is important to seek to reconcile this variation to support the effective development of programmes of care for this group of children and their families. The European Academy of Pediatrics (EAP) established a multidisciplinary Working Group on Complex Care and the initial work of this group examined how complex care is defined in the literature. A scoping review was conducted which yielded 87 papers with multiple terms found that refer to children living with complex needs. We found that elements of integrated care, an essential component of care delivery to these children, were repeatedly referred to, though it was never specifically incorporated into a term to describe complex care needs. This is essential for practice and policy, to continuously assert the need for integrated care where a complex care need exists. We propose the use of the term Complex and Integrated Care Needs as a suitable term to refer to children with varying levels of complexity who require continuity of care across a variety of health and social care settings.